2014
DOI: 10.1089/ten.tea.2012.0701
|View full text |Cite
|
Sign up to set email alerts
|

Adipogenic Factor-Loaded Microspheres Increase Retention of Transplanted Adipose Tissue

Abstract: The aim of this study was to develop and test a controlled delivery system of two adipogenic factors (insulin and dexamethasone [Dex]), to generate stable adipose tissue when mixed with disaggregated human fat. Both drugs were encapsulated in poly(lactic-co-glycolic acid), (PLGA) microspheres (MS) and mixed with human lipoaspirate to induce adipogenesis in vivo. It was hypothesized that the slow release of insulin and Dex would enhance both adipogenesis and angiogenesis, thus retaining the fat graft volume in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…44 Recent work has exploited poly(lactic-co-glycolic acid) (PLGA) systems for the delivery of anti-inflammatory drugs. [45][46][47][48][49][50][51][52][53] Higaki et al demonstrated that the continuous administration of betamethasone sodium phosphate through PLGA nanoparticles provided increased inhibition of inflammation in an experimental model of OA when compared with the same dosage of betamethasone sodium phosphate delivered three times through IA injection. 54 Dang et al demonstrated that dex releasing PLGA microparticles are capable of suppressing the host response to implanted polymer materials in a mouse model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…44 Recent work has exploited poly(lactic-co-glycolic acid) (PLGA) systems for the delivery of anti-inflammatory drugs. [45][46][47][48][49][50][51][52][53] Higaki et al demonstrated that the continuous administration of betamethasone sodium phosphate through PLGA nanoparticles provided increased inhibition of inflammation in an experimental model of OA when compared with the same dosage of betamethasone sodium phosphate delivered three times through IA injection. 54 Dang et al demonstrated that dex releasing PLGA microparticles are capable of suppressing the host response to implanted polymer materials in a mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…97,107,111,112 Additionally, this strategy has been shown to minimize the potential effects on the HPA axis, having been employed in vivo and shown to promote tissue formation with minimal systemic impact. 52 We further anticipate a strategy of chondroprotection where a glucocorticoid, administered from the locale of the injury/repair site in a manner that provides its sustained release at much lower levels than clinical injections, can also impact tissue healing and repair of the engineered graft upon implantation. 41,42 While future plans are aimed at further optimization of the dex microsphere strategy, including the testing of other proinflammatory cytokines such as TNF-a and the evaluation of tissue integrative repair in a cartilage explant ring model, [113][114][115] the efficacy of our approach on cartilage repair will necessarily have to be evaluated in vivo.…”
mentioning
confidence: 99%
“…14,15 Human lipoaspirate was processed as approved by the University of Pittsburgh Institutional Review Board, obtained by patients undergoing elective surgery using the Coleman method. 7,10 Adipose tissue was aspirated using a two-holed blunt harvesting cannula in combination with a 10-mL Luer-Lok syringe. The syringe was then centrifuged at 1200 g for 3 min.…”
Section: Methodsmentioning
confidence: 99%
“…Hematoxylin (Santa Cruz Biotechnology, Inc.) and eosin (Sigma-Aldrich) (H&E) staining was conducted using the same protocol as prescribed in previous study. 10 Vascularization of the extracted samples was determined by assessing a pan peroxidase-based CD31 antibody staining to confirm the presence of blood vessels using the same protocol as in the previous study. 10 …”
Section: Methodsmentioning
confidence: 99%
“…The establishment of vectoring delivery systems is necessary for ensuring Dex target the defect sites in the use of nanospheres. Although some microspheres and nanospheres have been served as delivery systems, conventional delivery methods are limited by the intrinsic inability to translate Dex into soft tissue engineering due to the un-controlled release [16][17][18]. Dex that is covalently immobilized into carriers can be more efficiently transported to a localized site and be released in a sustained-dosage form.…”
Section: Introductionmentioning
confidence: 99%